(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Background: Preferred technique of anaesthesia for caesarean section is neuraxial block. Hyperbaric bupivacaine in adequate dose for subarachnoid block often causes complications like hypotension, shivering, nausea, vomiting, chest pain and epigastric pain. Objectives: The aim of study is to reduce the complications of subarachnoid block, improve quality of block, quality of anesthesia, prolong duration of post operative analgesia by reducing total dose of local anaesthetics with the use of adjuvant like fentanyl or clonidine. Methods: Ninety parturients of ASA grade I & II for caesarean section under subarachnoid block were randomly allocated equally into three groups: Group B: hyperbaric bupivacaine 0.5% of 2 ml+ 0.25ml normal saline regarded as control Group BC: hyperbaric bupivacaine 0.5% of 1.75 ml + 0.5 ml clonidine (75 ?g) Group BF: hyperbaric bupivacaine 0.5% of 1.75 ml + 0.5 ml fentanyl (25 ?g) Parametric data like pulse, blood pressure among the groups were analyzed by ANOVA test & nonparametric data like chest discomfort, epigastric pain, nausea, vomiting were analyzed by chi-square test. Results: The study revealed that subarachnoid clonidine or fentanyl as adjuvant with low dose hyperbaric bupivacaine provide better quality of block, better quality of anaesthesia,more haemodynamical stability and longer duration of post operative analgesia compared to bupivacaine alone.Clonidine is better alternative to fentanyl as adjuvant with bupivacine in subarachnoid block. Conclusion: Addition of clonidine as adjuvant can reduce total dose of bupivacaine in subarachnoid block to ensure better quality of block, better quality of anaesthesia by reducing complications and longer duration of post operative analgesia compared to fentanyl. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12185 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 14-17